2001
DOI: 10.1152/jappl.2001.90.1.114
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular responses to nonrespiratory and respiratory arousals in a porcine model

Abstract: Spontaneous and provoked nonrespiratory arousals can be accompanied by a patterned hemodynamic response. To investigate whether a patterned response is also elicited by respiratory arousals, we compared nonrespiratory arousals (NRA) to respiratory arousals (RA) induced by airway occlusion during non-rapid eye movement sleep. We monitored mean arterial blood pressure (MAP), heart rate, iliac and renal blood flow, and sleep stage in 7 pigs during natural sleep. Iliac and renal vascular resistance were calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 40 publications
1
15
0
1
Order By: Relevance
“…Cardiac activation is typical of transient arousals and is correlated with the level of arousal and with a decrease in ␦EEG activity in NREM sleep (3,29,33,48,52,61). In this study, heart rate increase was only observed for the MA muscle.…”
Section: Arousal Level and Motor Activation In Nrem Sleepmentioning
confidence: 46%
“…Cardiac activation is typical of transient arousals and is correlated with the level of arousal and with a decrease in ␦EEG activity in NREM sleep (3,29,33,48,52,61). In this study, heart rate increase was only observed for the MA muscle.…”
Section: Arousal Level and Motor Activation In Nrem Sleepmentioning
confidence: 46%
“…Many experiments involve a tracheotomy with an intermittently occluded endotracheal tube. Thus far, these techniques have been used in dogs (15), lambs (16), baboons (17), piglets (18,19), and rats (20). A dog model of OSA is depicted in Figure 2, in which a computer-controlled valve would close upon detection of a predetermined period of sleep.…”
Section: Surgical/mechanical Modelsmentioning
confidence: 99%
“…The neural site(s) responsible for this adaptive increase in BP is not known; however, it is reasonable to speculate that the sympathoexcitatory region in the rostral ventrolateral medulla is likely a potential site of adaptation. A porcine model of OSAHS indicates that arousals may increase peripheral vascular constriction, muscle vasodilation, and visceral vasoconstriction [78,79]. In humans, arousals and sleep disruption could be important factors in acute and chronic BP changes with apneas [80].…”
Section: Discussionmentioning
confidence: 99%